VERBAL AGGRESSION IN INDONESIAN SOCIAL MEDIA DISCOURSE: A QUALITATIVE ANALYSIS OF FACEBOOK POSTS - Sofyan, Ryan Rayhana; Hasriani, Hasriani; Sakaria, Sakaria (Universitas Negeri Makassar, 2024)
This study investigates the phenomenon of verbal aggression in posts on social media platforms, particularly Facebook, in Indonesian language. The research applied a qualitative descriptive methodology to explore the ways in which verbal aggressiveness manifests in user conversations within a specific linguistic and cultural specific context. The analysis, based on Pierre Bourdieu's Symbolic Violence theory, aims to identify several types and interpretations of verbal aggression, including hyperbole, euphemism, dysphemism, stigmatization, and association. The results indicate that Indonesian Facebook users often employ these linguistic tactics to express aggression in a subtle or explicit manner. This study not only classifies the various forms of verbal aggressiveness commonly found in Indonesian Facebook conversations, but also analyzes the social and cultural elements that shape these interactions. The study emphasizes the significance of comprehending cultural subtleties in verbal aggression in digital communication, which could be advantageous in formulating improved social media communication rules and cultivating a more courteous online interaction environment.